Generating Multistructured Ultrasound via Bioinspired Metaskin Patterning for Low‐Threshold and Contactless Control of Living Organisms. (31st May 2022) - Li, Peng‐Qi; Li, Zong‐Lin; Zhou, Wei; Wang, Shengwu; Meng, Long; Peng, Yu‐Gui; Chen, Zhi; Zheng, Hairong; Zhu, Xue‐Feng
Abstract: Metasurfaces of the subwavelength thicknesses provide a distinctive route for acoustic wave manipulation. Based on the advanced 3D printing, those judiciously designed 2D metamaterials enable intriguing effects such as abnormal reflection, transmission, and absorption. However, acoustic metasurfaces, with strong wave–structure interactions in subwavelength scales, have encountered a big challenge of being acoustically transparent due to the insufficient impedance mismatch underwater. Here, reconfigurable bioinspired metaskin patterning for generating multistructured waterborne ultrasound is proposed. The nanostructured metaskin exhibits the "lotus effect, " with the thickness of only 70 μm (≈1/20 wavelength at 1 MHz) and a tremendous impedance mismatch (≈0.0001 transmission) for ultrasound. By depositing the strippable metaskins via self‐assembly into different patterns, the focusing, the vortex, and the Talbot structured ultrasound beams are implemented, respectively. The multistructured ultrasound has the patterned intensity fields of energy redistribution, where even weak field enhancement at low frequencies can activate the living organisms directly without using microbubbles, which enables low‐threshold and contactless behavior control via the mechanical stimulus. Abstract : Bioinspired metaskins with reconfigurable patterning enable the generation of various structured ultrasound beams, where local field enhancements can activate the living organisms directly and enable contactless behavior control, providing a noninvasive approach for versatile practical applications in neurostimulation on targeted neurons in vivo.